On the increasing incidence of SARS-CoV- 2 in older adolescents and younger adults during the epidemic in Mexico - Dalia Stern; Martin Lajous; Blanca De la Rosa; Edward Goldstein (Instituto Nacional de Salud Pública, 2021)
Objective. To estimate temporary changes in the incidence of SARS-CoV-2-confirmed hospitalizations (by date of symptom onset) by age group during and after the national lockdown. Materials and methods. For each age group g, we computed the proportion E(g) of individuals in that age group among all cases aged 10-59y during the early lockdown period (April 20-May 3, 2020), and the corresponding proportion L(g) during the late lockdown (May 18-31, 2020) and post-lockdown (June 15-28, 2020) periods and computed the prevalence ratio: PR(g)=L(g)/E(g). Results. For the late lockdown and post-lockdown periods, the highest PR values were found in age groups 15-19y (late: PR=1.69, 95%CI 1.05,2.72; post-lockdown: PR=2.05, 1.30,3.24) and 20-24y (late: PR=1.43, 1.10,1.86; post-lockdown: PR=1.49, 1.15,1.93). These estimates were higher in individuals 15-24y compared to those ≥30y. Conclusions. Adolescents and younger adults had an increased relative incidence of SARS-CoV-2 during late lockdown and post-lockdown periods. The role of these age groups should be considered when implementing future pandemic response efforts.